Beyond evolution : human nature and the limits of evolutionary explanation - O'Hear, Anthony (Clarendon Press, 1999)
In this controversial book O\'Hear takes a stand against the fashion for explaining human behavior in terms of evolution. He contends that while the theory of evolution is successful in explaining the development of the natural world in general, it is of limited value when applied to the human world. Because of our reflectiveness and our rationality we take on goals and ideals which cannot be justified in terms of survival-promotion or reproductive advantage. O\'Hear examines the nature of human self-consciousness, and argues that evolutionary theory cannot give a satisfactory account of such distinctive facets of human life as the quest for knowledge, moral sense, and the appreciation of beauty; in these we transcend our biological origins. It is our rationality that allows each of us to go beyond not only our biological but also our cultural inheritance: as the author says in the Preface, \"we are prisoners neither of our genes nor of the ideas we encounter as we each make our personal and individual way through life.\"
Keywords: psychologie, klinická psychologie; Biological Evolution; biologická evoluce; biologie